PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH MELALUI PROGRAM PELATIHAN DAN PENDAMPINGAN USAHA DI PONDOK BAHAR KECAMATAN KARANG TENGAH KOTA TANGERANG - Lisnah Lisnah; Dafyar Eliadi H; Edi Mulyadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
This study aims to analyze the Empowerment of Micro, Small and Medium Enterprises through Training and Business Assistance Programs at Pondok Bahar, Karang Tengah Subdistrict, Tangerang City. This research is motivated by the existence of micro, small and medium enterprises in Pondok Bahar which experience several problems such as the existence of limited capital and lack of access to banking, lack of understanding of business management management for new entrepreneurs, especially those related to financial management, lack of mastery of digital promotional media to develop businesses and still lack of coaching, management guidance and improvement of human resources of micro, small and medium enterprises. The concept to measure empowerment uses the stages of empowerment, namely determining the work area, socialization, implementing activities, organizing, awareness, advocacy and politicization, while to describe training using the parameters of training participants, trainers, materials and methods. Then to describe mentoring using the parameters of facilitation, strengthening, protection, and maintenance. Qualitative research methods were used to answer the research problems that had been formulated. Data analysis used observation, interview and documentation techniques. The interview technique was conducted to research informants who were taken deliberately, while the observation technique. The results of the study provide a suggestion that the Department of Industry, Trade, Cooperatives and Micro Small Enterprises can facilitate and encourage micro and small entrepreneurs so that their products can be sold at Alfamart, Indomaret and Alfamidi in their area, by facilitating the legality of licensing from product brand patents, licensing to obtain halal certificates, the process of making Entrepreneurial Identification Numbers and halal certificates so that the products of micro and small entrepreneurs meet the requirements in terms of packaging and production to be sold by Alfamart, Indomaret and alfamidi. Keywords: Empowerment, Training, Mentoring and Micro, Small and Medium Enterprises